Anti-lipase Activity of Kemuning (Murraya paniculata) Leaves Extract and Its Fractions - Nuri Nuri; Tazkiyatul Fitriyah; Endah Puspitasari; Bawon Triatmoko; Dewi Dianasari (Journal of Agromedicine and Medical Sciences, 2024)
Kemuning (Murraya paniculata) belongs to the Rutaceae family, it grows a lot in tropical areas such as Indonesia. Traditionally, Kemuning leaves are used for weight loss preparations and are believed to contain compounds that can inhibit pancreatic lipase, including flavonoids. This study aimed to reveal the antilipase activity of Kemuning leaves extract and its fractions. The extraction of Kemuning leaves was carried out by maceration with 70% ethanol as solvent. The vacuum liquid chromatography method was used to separate the secondary metabolites in the extract with the stationary phase of silica gel and the eluent mixture of n-hexane, ethyl acetate, and methanol in a gradient manner. Meanwhile, the antilipase activity was tested by colorimetric method, with p-nitrophenyl butyrate as a substrate and orlistat as a positive control. The extract obtained was 19.94% of the weight of the simplicia. The separated extract was collected in 20 flasks and then combined based on the Rf value of the spots observed on thin layer chromatography (TLC) producing 8 fractions (fractions A-H). The percentage yields of fractions A-H were 1.20, 1.33, 1.80, 3.92, 3.57, 4.20, 16.85, and 14.47%, respectively. Antilipase activity was indicated by IC50 values, which were 17.603 ± 1.660 and 108.554 ± 1.660 µg/mL for orlistat and extract, respectively. The antilipase activities of fractions A-H were 130.19 ± 2.90, 119.52 ± 1.95, 96.95 ± 1.81, 91.65 ± 0.78, 95.30 ± 1.46, 114.76 ± 2.87, 127.07 ± 3.56, and 134,04 ± 3.16 µg/mL, respectively. Based on these results, it can be concluded that the extract and its fractions exhibit very strong antilipase activity. Keywords: Murraya paniculata; extract; fraction; antilipase